Change in Dysfunctional Sleep-Related Beliefs is Associated with Changes in Sleep and Other Health Outcomes Among Older Veterans With Insomnia: Findings From a Randomized Controlled Trial. Issue 1 (4th May 2021) - Song, Yeonsu; Kelly, Monica R; Fung, Constance H; Dzierzewski, Joseph M; Grinberg, Austin M; Mitchell, Michael N; Josephson, Karen; Martin, Jennifer L; Alessi, Cathy A
Abstract: Background: Cognitive behavioral therapy for insomnia (CBTI) targets changing dysfunctional sleep-related beliefs. The impact of these changes on daytime functioning in older adults is unknown. Purpose: We examined whether changes in sleep-related beliefs from pre- to post-CBTI predicted changes in sleep and other outcomes in older adults. Method: Data included 144 older veterans with insomnia from a randomized controlled trial testing CBTI. Sleep-related beliefs were assessed with the Dysfunctional Beliefs and Attitudes about Sleep-16 (DBAS-16, subscales: Consequences, Worry/Helplessness, Sleep Expectations, Medication). Outcomes included sleep diary variables, actigraphy-measured sleep efficiency, Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), Flinders Fatigue Scale (FFS), Patient Health Questionnaire-9, and health-related quality of life. Analyses compared slope of change in DBAS subscales from baseline to posttreatment between CBTI and control, and assessed the relationship between DBAS change and the slope of change in outcomes from baseline to 6 months. Results: Compared to controls, the CBTI group demonstrated stronger associations between improvement in DBAS-Consequences and subsequent improvement in PSQI, ISI, ESS, and FFS. The CBTI group also demonstrated stronger associations between improvement in DBAS-Worry/Helplessness and subsequent improvements in PSQI, ISI, and FFS; improvements in DBAS-Medication and PSQI; and improvements in DBAS-Sleep Expectations and wake after sleep onset (sleep diary) and FFS (all p < .05). Conclusions: Significant reduction in dysfunctional sleep-related beliefs following CBTI in older adults predicted improvement in several outcomes of sleep and daytime functioning. This suggests the importance of addressing sleep-related beliefs for sustained improvement with CBTI in older veterans. Trial Registration: ClinicalTrials.gov Identifier: NCT00781963. Abstract : Improvement in specific types of sleep-related beliefs was associated with greater improvements in sleep and daytime functioning after cognitive behavioral therapy for insomnia among older veterans with insomnia.